Pengaruh Pemanfaatan Sistem Informasi Akuntansi, Pemanfaatan Teknologi Informasi, Sistem Pengendalian Intern Dan Kompetensi Akuntansi Terhadap Kualitas Laporan Keuangan Pada Lembaga Perkreditan Desa Sekecamatan Tampaksiring - Ni Kadek Nita (Hita Akuntansi dan Keuangan, 2023)
This study discusses the relationship or relevance between the use of accounting information systems, the application of the use of information technology, internal control systems, and accounting knowledge to the quality of financial reporting. A survey sample of 128 respondents was distributed to collect data. Using the linear regression analysis method, we confirmed that the accounting information system does not affect the quality of financial reporting. The use of information technology, internal control systems and accounting knowledge affect the quality of financial reporting.